2021
DOI: 10.1073/pnas.2023456118
|View full text |Cite
|
Sign up to set email alerts
|

Conditional destabilization of the TPLATE complex impairs endocytic internalization

Abstract: In plants, endocytosis is essential for many developmental and physiological processes, including regulation of growth and development, hormone perception, nutrient uptake, and defense against pathogens. Our toolbox to modulate this process is, however, rather limited. Here, we report a conditional tool to impair endocytosis. We generated a partially functional TPLATE allele by substituting the most conserved domain of the TPLATE subunit of the endocytic TPLATE complex (TPC). This substitution destabilizes TPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 67 publications
1
45
1
Order By: Relevance
“…To test this notion, we looked directly at CCVs in plant cells subjected to TPC disruption. For these studies, we used the inducible TPLATE loss-offunction mutant WDXM2 in which tplate mutant plants are complemented with a genetically destabilized version of TPLATE that after heat shock results in the total aggregation of TPLATE away from the PM and blocks CME (23). First, we further confirmed that heat shock treatment had no significant effect on the efficiency and kinetics of CME in plants by examining FM4-64 uptake and the dynamics of single CME events (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…To test this notion, we looked directly at CCVs in plant cells subjected to TPC disruption. For these studies, we used the inducible TPLATE loss-offunction mutant WDXM2 in which tplate mutant plants are complemented with a genetically destabilized version of TPLATE that after heat shock results in the total aggregation of TPLATE away from the PM and blocks CME (23). First, we further confirmed that heat shock treatment had no significant effect on the efficiency and kinetics of CME in plants by examining FM4-64 uptake and the dynamics of single CME events (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Thus, to test if the TPC itself could be involved in membrane remodeling, we purified the EH domains of the TPC member AtEH1/Pan1 and showed that they have intrinsic membrane-remodeling activity in vitro, therefore demonstrating that the TPC possess membranebending machinery. However, how this activity could be mediated in vivo remains an open question, as AtEH1/Pan1 remains associated with the PM following TPC disruption (23) but is not sufficient to generate the invagination (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…To test this notion, we looked directly at CCVs in plant cells subjected to TPC disruption. For these studies, we used the inducible TPLATE loss-of-function mutant WDXM2; where tplate mutant plants are complemented with a genetically destabilized version of TPLATE that after heat shock results in the total aggregation of TPLATE away from the PM and blocks CME (20). First, we further confirmed that the heat shock treatment had no significant effect on the efficiency and kinetics of CME in plants by examining FM4-64 uptake and the dynamics of single CME events (Fig.…”
mentioning
confidence: 73%
“…This demonstrated that AtEH1/Pan1 has the capacity to contribute to membrane bending. However, as AtEH1/Pan1 remains associated with the PM during WDXM2 disruption (20), but is not sufficient to generate the invagination (Fig. 3), it suggests that additional factors are required to modulate the membrane bending activity of the AtEH1/Pan1 EH domains.…”
mentioning
confidence: 99%
“…Plants have shown evolutionary divergence in their key EAPs compared to other model systems including, for example, the TPLATE complex (TPC), which likely evolved in early eukaryotes but is notably absent from yeast and metazoans and which is essential for plant clathrin-mediated endocytosis (Gadeyne et al, 2014;Hirst, et al, 2014;Wang, et al, 2021;Bashline, et al, 2015). Similar to AP-2, TPC functions exclusively at the PM and acts as a central interaction hub required for the formation of endocytic CCVs (Gadeyne, et al, 2014;Wang, et al 2016;Zhang, et al, 2015;Yperman, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%